STRATEGIC GAMIFICATION FOR RELIGIOUS LEARNING: AN EMPIRICAL LITERATURE REVIEW - Nur ‘Atieqah Mohd Zainudin; Miftachul Huda (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
This study aims to empirically examine the effectiveness of gamification strategies in religious learning as well as identify the challenges and opportunities that exist in efforts to enrich the learning experience of students under the Dini Integrated Curriculum known as Kurikulum Bersepadu Dini (KBD). Through a comprehensive and detailed literature review, this study analyzes the use of innovative gamification elements such as artificial intelligence (AI), augmented reality (AR), and advanced multimedia support in increasing students’ motivation and interest in learning religion in Arabic Language. The results of the study show that the integration of this technology with traditional gamification elements such as points, badges, and leaderboards can trigger deeper student engagement and improve learning effectiveness. Students show a higher interest in learning activities and the ability to understand and remember religious concepts more deeply and effectively. However, this study also identified several challenges in the implementation of gamification, including the urgent need for comprehensive training and professional development for teachers as well as the provision of sound technological infrastructure and technical support in schools. By providing practical guidance and detailed recommendations for teachers, this study aims to assist in the application of effective gamification techniques in religious teaching, particularly in the context of KBD. This study concludes that gamification, if applied with the right strategy, has great potential to enrich the religious learning experience and achieve comprehensive and holistic educational goals under KBD, further fostering a generation of more knowledgeable and highly motivated students. With this, it is hoped that religious teaching can become more dynamic, interesting and relevant to today’s young generation, as well as fulfilling the aspirations of the National Education Philosophy, the Islamic Education Philosophy and the Malaysian Education Development Plan.